High-risk HPV DNA status and p16 (INK4a) expression as prognostic markers in patients with squamous cell cancer of oral cavity and oropharynx - Śnietura, Mirosław; Jaworska, Magdalena; Pigłowski, Wojciech; Goraj-Zając, Aleksandra; Woźniak, Grzegorz; Lange, Dariusz (Polish Journal of Pathology, 2010)
Aim of the study : To determine and compare the influence of the HPV DNA status and p16(INK4a) expression on the outcome of postoperative radiotherapy for squamous cell cancer of the oral cavity or oropharynx. Material and methods : 59 patients with high-risk squamous cell cancer of the oral cavity or oropharynx were enrolled. They underwent major surgery and postoperative radiotherapy. The HPV DNA status and p16(INK4a) expression were assessed with QPCR and immunohistochemistry and correlated with loco-regional control and overall survival. Results : 15.3% of tissue samples were HPV positive. All positive patients were identified with HPV16 subtype infection, and no other subtypes of high-risk HPV were detected. 5-year LRC in HPV(+) patients was 100%, compared to 50% in the HPV(–) group. 17.9% of all samples had evident p16(INK4a) expression. Among HPV(+) cases, 55.6% showed p16(INK4a) expression. 5-year LRC in patients with p16(INK4a) expression was 89%, compared to 51% in the p16(INK4a) negative group but this tendency was not significant (p = 0.055). Conclusion : These data show that the HPV status is a good predictor of loco-regional control and overall survival in patients treated with radical surgery and adjuvant radiotherapy. The study shows a strong correlation between high-risk HPV infection and p16(INK4a) expression, but detection of viral DNA with QPCR has stronger prognostic potential.